DYNAMIC SYSTEM MODEL OF THE EFFECT OF TPS 3R AND WASTE BANK TO WASTE REDUCTION IN GORONTALO - Magfirah Badu, Maya
The increasing amount of waste every year in Gorontalo City is one of the waste management issues. In the year 2020, the waste handling level is reaching 53%, but the waste-reducing is still around 3,9%. The efforts to increase the reduction level by the government is to make 3R facilities such as TPS 3R and waste ban, but some of its units are not running well. Various efforts to reduce the amount of waste in Gorontalo City are still developing and should be evaluated. This research aims to model the dynamic of waste management related to the effect of TPS 3R and waste bank on the waste reduction in Gorontalo City. The dynamic model system is related to the behavior affected by time. Data collection is done by observation, interview, and questionnaire. The results of the BaU simulation show that there is an increase in a waste generation because of the increase in population, but this existing condition of waste management can not affect the reduction of waste in the future. After running a moderate scenario simulation with the intervention by increasing the processing waste in the waste bank and TPS 3R and by increasing the rate of TPS 3R growth member, the unmanaged waste is reduced to 0%, and the reducing level reaches 12,64 % by the year of 2030. The optimistic scenario developed to reach the Jakstrada target shows that the intervention can reach the target of waste reduction and waste handling so that the unmanaged waste will reach 0% by the year 2025. Based on those scenarios, it can be concluded that the optimistic scenario is the best scenario. Still, the moderate scenario also will become a good option as the first step to reaching the target of waste reduction in Gorontalo City.